Anthropometric Measurement of External Ear and Correlation with Age in North Regional People of Bangladesh - Asadujjaman, Md; Rashid, Md Harum Or; Rana, Sohel (Bangladesh Journal of Medical Science, 2019)
Objective: The purpose of this study was to build an external ear anthropometric database in North regional people of Bangladesh. This study also aimed to show the morphological variations between male and female as well as changes in ear anthropometry with age. Materials and Methods: Ear dimensions of 313 people (150 male and 163 female), aged between 18-75 years, were measured pursuant to standard anthropometric measurement procedure. A total of five external ear dimensions- ear length, ear breadth, base of the auricle, lobe length and lobe breadth was measured. Pearson correlation coefficient was used to determine the relationship among various ear measurements, and linear regression analysis was used to estimate ear dimensions from the age of the people. Result: All ear dimensions were found larger in male than in women. The result also revealed that, dimensions of ear parameters increase proportionally with the increase of age, except male left-lobe breadth and female lobe breadth in both sides. Conclusion: Of course, this study of human ear morphology will serve as a quantitative database and play an enormous importance of anatomy and human factors engineering point of view. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.206-210